2002
DOI: 10.1381/096089202762252424
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery in a Patient with Possible Psychiatric Contraindications

Abstract: Grade III obesity (BMI > 39.9 kg/m2) is considered a chronic disease where clinical and diet therapy show poor results, with high rates of relapse. The most consistent results are those obtained through surgical procedures. Several authors discuss the contraindications for the performance of anti-obesity operations. Psychiatric disorders are often considered contraindications to these operations, especially affective disorders, psychotic disorders and personality disorders. The authors report the case of a 37-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
0
3
0
6
Order By: Relevance
“…38,50 Thus, many authors do not contraindicate obesity surgery based on psychiatric disorders, provided that there is adequate preand postoperative psychiatric support. 48,83 In addi-tion, some workers suggest that, because candidates for bariatric surgery frequently show high levels of psychopathology, if subjects were excluded because of a history of psychiatric illness, few patients would be eligible for surgery. 48 There are even some studies that suggest that a history of having received treatment for a psychiatric disorder or substance abuse may be prognostic of favorable outcome; perhaps having participated in successful treatment may have assisted individuals in the development of skills for lifestyle change.…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…38,50 Thus, many authors do not contraindicate obesity surgery based on psychiatric disorders, provided that there is adequate preand postoperative psychiatric support. 48,83 In addi-tion, some workers suggest that, because candidates for bariatric surgery frequently show high levels of psychopathology, if subjects were excluded because of a history of psychiatric illness, few patients would be eligible for surgery. 48 There are even some studies that suggest that a history of having received treatment for a psychiatric disorder or substance abuse may be prognostic of favorable outcome; perhaps having participated in successful treatment may have assisted individuals in the development of skills for lifestyle change.…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…Contudo não há dados precisos nem fatores preditivos de bom ou mau prognóstico adequadamente estudados e/ou comprovados. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Esta é uma área de interesse, não só do ponto de vista científico como também clínico.…”
Section: Contra-indicações De Tratamento Cirúrgico Para Obesidade Mórunclassified
“…21,[28][29][30][38][39][40][41][42] Os resultados promissores não significam que pacientes candidatos às operações não necessitem de correto acompanhamento psicológico e psiquiátrico nas diversas fases do tratamento bariátrico. Estes pacientes apresentam maior associação com quadros psiquiátricos e o não tratamento adequado das patologias pode ameaçar seu prognóstico.…”
Section: Contra-indicações De Tratamento Cirúrgico Para Obesidade Mórunclassified
“…During infancy the existence of childhood psychopathology tends to be higher among clinical populations of obese children and adolescents, and the major psychological consequences of obesity are low self-esteem, poor social interaction, depression and control disturbance 18 . Some authors report that at the level of psychological disorders, the most common is depression, and also the anxiety disorders 19,20 . A longitudinal study developed by Mustillo and colleagues with 991 children aged 9 to 16 years has shown that childhood obesity was not associated with problems of depression, with only the group with chronic obesity had psychiatric problems 21 .…”
Section: Psychological Morbidity and Childhood Obesitymentioning
confidence: 99%